An improved methodology for efficient isolation of mesenchymal stem cells from Caprine bone marrow - PATHAK, JUHI; KHARCHE, SURESH DINKAR; SIKARWAR, ANUJ KUMAR SINGH; JENA, DAYANIDHI; SINGH, SHIVA PRATAP; RANJAN, RAVI (The Indian Journal of Animal Sciences, 2021)
The aim of this study was to investigate the effect of increasing volume of bone marrow (BM) aspirate of goats on yield of mesenchymal stem cells (MSCs). For this, yield of MSCs in seven groups (Gr; 1-7 Grs, including a control Gr) were compared. After isolation and enrichment of BM MSCs with density gradient centrifugation using increasing volume of Histopaque-1077, the properties of MSCs to adhere the plastic surfaces and expression of alkaline phosphatase (ALP) were used for the identification of MSCs. The results indicated that 18 ml of BM aspirate (Gr 5) provided maximum number of MSCs using 3 ml of histopaque compared to the control and other Gr. The yield in Gr 5 was about 4.4 folds higher compared to the control Gr. In conclusion, these results demonstrated that in a single procedure the modified protocol yield significantly higher number of caprine MSCs from goat BM aspirate compared to the standard protocol. Thus, it can be used for isolation of more number of MSCs from a large quantity of bone marrow with least volume of consumables required for density-gradient centrifugation.